Temas y pensamiento en el poema "Espacio" de Juan Ramón Jiménez: el cronotopos tiempo-espacio, Dios, el cuerpo de la conciencia y el amor - Rastrollo Torres, Juan José (El Colegio de México, 2017)
Reception: May 29, 2016Accepted: November 23, 2016Octavio Paz once wrote that Juan Ramon Jimenez’s poem Espacio was “a monument of contemporary poetic consciousness”. This long poem certainly goes far beyond most of the Spanish poetry written in the 20th century and universalizes the Spanish poetic tradition by putting it into contact with modern literary trends. But if Espacio is so outstanding, it is because it is a poem of inexhaustible mystery, with the result that each rereading forges new lines of interpretation. The present study attempts to define these hermeneutical lines, distinguishing between the motifs (the sea, the woman, the tree, the bird, the dog…), the subject (the anecdotes in the poem) and the themes (such recurring concerns as time-space, god, consciousness and love, which all gravitate around the central theme of consciousness, seen as individual self-knowledge).